Factors Affected Recovery Time Of Residents With Covid-19 - Firdawsyi Nuzula; Maulida Nurfazriah Oktaviana ((JKG) Jurnal Keperawatan Global, 2022)
Background: The massive spread of Covid-19 and made it a pandemic causing a lot of fear and anxiety among people around the world. Covid-19 has been a global disaster which has a high level of spread and severity since it is a contagious disease. The severity of this disease ranges from asymptomatic to severe with general symptoms of fever and cough and causing acute respiratory distress syndrome, especially in the elderly and people with comorbidity. Family support helps patients to meet their basic needs and can help to increase the spirit to recover which is one of the factors that accelerate the patient’s recovery process. Methods: Population in this study consisted 660 residents who had confirmed Covid-19 and 109 samples were taken with purposive sampling technique appropriately to inclusion criteria. Independents variables in this study consisted of history of co-morbidities, knowledge, family support and motivation to recover. While the dependent variable is the healing time of Covid-19. The instrument of this study used a questionnaire sheet. This is a correlational study with cross sectional quantitative analytic. Results: Bivariate analytic show that only family support variable has significant results with p value <0,05. Family support is the determinant factors with p value of 0,0017 compared with other factors such as comorbid, knowledge and motivation. Conclusion: It can be conclude that family support is the determinant of recovery time of people affected by Covid-19. The most needed support for healing in the form of being sufficient and meeting the needs during ilness, both physically and psychologically.